Indian Costumes through the Ages: Insights into Sartorial Choices Using Mathematical Biology. (16th May 2021) - Raghavan, M.; Maigur, R. K.
Abstract : Costumes of a civilization are studied as a means of understanding people, their thinking, tastes, and culture. However, the subjective 'feel' of costume due to their interaction with human body is an important personal aspect of costumes that has not been studied. We hypothesize that this aspect can explain the motivation behind features of costumes that change or remain immutable over time. We propose a novel numerical encoding of costumes based on the interaction of costumes with human anatomy. Using methods from machine classification on a set of costumes from ancient to contemporary periods, we show that costumes of different epochs and cultures are separable in the two dimensional principal component space. We use the Eigen costumes to analyze the immutable similarity in Indic costumes through the ages and the contrasting features between Indic and non‐Indic. We further dwell into primary sources to demonstrate that these characteristic features of Indic costumes were very likely considered and deliberate choices motivated by yoga in order to induce beneficial effects on prāṇa . We hope that this work will be a small first step for an alternate way of deriving insights into sartorial trends in various archeological specimen using methods from life sciences and computation.